Materiality in picturebooks : an introduction - Veryeri Alaca, Ilgım (Array, 2019)
Through this special issue, we seek to explore the educational, creative, and intimate qualities of materials and structures in picturebooks in emerging and existing book formats. From hornbooks to iPads, children’s reading experiences have been mediated via transforming book systems in ways serving to educate, to entertain, and to facilitate narrative. Material and sensory aspects of picturebooks also have the capacity to act as a third narrative system, operating besides words and images. These aspects may engage and challenge the child to comprehend a subject through the experiential handling of the picturebook, resulting in an embodied meaning-making process. Physical interactions may be explored further in printed as well as digital picturebooks with the rise of multimodal literacies supported by novel technologies that can cater for diverse needs. This special issue stems from a workshop entitled “The Material, Spatial and Sensory Encounters with the Picturebook Object” which took place at Koç University, İstanbul, in June 2017. It builds on the exchanges facilitated by the workshop, and aims to reflect on how book systems alter the way children perceive texts.